Fishing technology and fisherman community: a narrative review - Fadzil, Mohd Fauzi; Idris, Khairuddin; Bolong, Jusang; Samsuddin, Samsul Farid (Human Resource Management Academic Research Society, 2019)
The limited number of existing studies on the use of fishing technologies among fishermen community has driven this narrative review article to discuss the matter within the Malaysian context. Four social sources, namely family members, fishermen colleagues, agencies, and village administration members are found to have influence on fisherman behavior and decision towards fishing technology usage. Later in the article, the benefits and obstacles of using fishing technology usage are discussed. This paper offers insights and recommendations such as restructuring fisherman allowance, providing fishing equipment (technology), and providing training funds to attend workshops or programs on how to use and handle fishing technology tools. These suggestions will encourage the fishermen community to utilize fishing technology in their fishing routines.